Identification and Optimization of Indole-3-Acetic Acid Production of Endophytic Bacteria and Their Effects on Plant Growth - Saowapar Khianngam; Pimjai Meetum; Pantipa Na Chiangmai; Somboon Tanasupawat (Tropical Life Sciences Research, 2023)
Indole-3-acetic acid (IAA) is one of the most physiologically active auxins produced by rhizobacteria and is potentially applied for agriculture. Two endophytic bacteria, VR2 and MG9, isolated from the root of Chrysopogon zizanioides (L.) collected at Cha-Am, and the leaf of Bruguiera cylindrica (L.) Blume collected from a mangrove forest at Ban Laem, Phetchaburi Province, Thailand, were taxonomic characterised based on their phenotypic characteristics and 16S rRNA gene analysis. Strain VR2 was closely related to Enterobacter hormaechei CIP 103441T (99.6% similarity), while strain MG9 was closely related to Bacillus aryabhattai B8W22T (99.9% similarity). Consequently, they were identified as Enterobacter hormaechei and Bacillus aryabhattai, respectively. The IAA production of VR2 and MG9 strains are determined and applied to rice seeds for their root and shoot germination. Strains VR2 and MG9 greatly produced a yield of IAA, 246.00 and 195.55 µg/mL in 1,000 µg/mL of L-tryptophan at pH 6 for 48 h. They showed no significant differences in IAA to root and shoot development. However, the bacterial IAA exhibited potential nearby synthetic IAA, which had a significant effect compared to the control. IAA produced from these two strains might preferably trim down the use of synthetic IAA and could contribute to sustainable agriculture.